If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -2 = 4(2y + -3) Reorder the terms: -2 + 3y = 4(2y + -3) Reorder the terms: -2 + 3y = 4(-3 + 2y) -2 + 3y = (-3 * 4 + 2y * 4) -2 + 3y = (-12 + 8y) Solving -2 + 3y = -12 + 8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8y' to each side of the equation. -2 + 3y + -8y = -12 + 8y + -8y Combine like terms: 3y + -8y = -5y -2 + -5y = -12 + 8y + -8y Combine like terms: 8y + -8y = 0 -2 + -5y = -12 + 0 -2 + -5y = -12 Add '2' to each side of the equation. -2 + 2 + -5y = -12 + 2 Combine like terms: -2 + 2 = 0 0 + -5y = -12 + 2 -5y = -12 + 2 Combine like terms: -12 + 2 = -10 -5y = -10 Divide each side by '-5'. y = 2 Simplifying y = 2
| 13+3x=-29-3n | | 2.6=0.2-4 | | -2a+(5a-3)-(3a+4)= | | 8-3k+6k=2k-3 | | -4(x+3)-7=-3x-15 | | 6(w-3)-(2w-5)=3w | | y=-8/9x-8/9 | | -5+7x+7=8(x+3)-9 | | 12R=1/4M-5 | | 4x-28y=44 | | -2y+13=14-y | | g(p+2)=3x^2+3x+1 | | -2-k=-8 | | -4c+18=5c | | (1/3)9squarred | | 7x+8-5x=-2 | | 7b+3=5b-11 | | -6+6x+7=(x+1)-2 | | -40-8=6s | | -2=0-1/5j | | 9-5a+a=-3 | | 6n-7(n-1)=12 | | 2m+6=2m-2 | | 5(z+6)=2+3z | | (6/5(p-4))-(6/5p) | | 0=16t^2+138t+55 | | 6a+2a+12=7+6a+3 | | 4x-5+2x=13 | | y=4x^2-6x-7 | | 0=16t^2+138t+c | | x^2-y^2=50 | | x+8+5x=2-2x |